Multi agent monitoring system - Maung, Myo Minn Minn. (2010)
Agent technology has evolved from research interest stage into practical implementation stage. At first, there were lots of research work on agent modeling but the deployment of agent systems is still lacking. Multi Agent Development Environment (MADE) is designed to bridge the gap between initial system design and agent implementation. Agents also need to interact with each other in the multi agent environment systems to solve common problem in order to achieve individual or shared goals. FIPA has standardized Agent Communication Language (ACL) for agent communications. Though agent deployment system and agent communication protocol has established this far, there is still a lack of widespread use on multi agent monitoring system. In agent deployment environment, the mental states, transitions, goal achieved, task performed for each agent are needed to monitor. This can be achieved through multi agent monitoring system. But practical software to monitor the agent mental state is rare. This can be due to practical tools or software not easily available currently to monitor the agents or agent monitoring system needs to collaborate with the agent development environment and there are not many development environment exists. Likewise, the exact definition on what multi agent monitoring system should perform in order to achieve the monitoring purpose is not exactly defined. The purpose of this report is to address the key issues and challenges in developing such a multi agent monitoring system.